Unions as Insurance: Employer–Worker Risk Sharing and Workers' Outcomes during COVID-19 - Nils Braakmann; Boris Hirsch (Institute of Labor Economics (IZA), 2023)
We investigate to what extent workplace unionisation protects workers from external shocks as predicted by models of implicit contracts. Using the COVID-19 pandemic as a plausibly exogenous shock hitting the whole economy, we compare workers who worked in unionised and non-unionised workplaces directly before the pandemic in a difference-in-differences framework. We find that unionised workers were substantially more like to remain working for their pre-COVID employer, at their pre-COVID workplace, in their pre-COVID job and to be in employment. This greater employment stability was not traded off against lower working hours or labour income.
Keywords: J51; I18; I19; J63; 330; unions; risk-sharing; implicit contracts; insurance effects; COVID-19